Scenario of Solid Waste Management in Indian Cities - Poulomee Ghosh; Eshwar Reddy Bobba; Sai Sanjay Dodda; Vamsi Krishna Jasti; Sarvan Meka; Hasitha Reddy Vanga (Ecology, Economy and Society – The INSEE Journal)
The quantum of solid waste generated by the world is growing with increasing development and changing lifestyles, making waste management a daunting challenge. The Solid Waste Management Rules, 2016, of India, along with initiatives by the Smart City Mission and Swachh Bharat Abhiyan, are pivotal in encouraging sustainable waste management. This paper establishes progress, gaps, and ground realities in solid waste management (SWM) in three of the best-performing cities in India. The paper first documents trends and practices in SWM in the three cities and then cross-checks the ground scenario through a primary survey of 322 citizens. The results show that all three cities have experienced improvements in SWM following government initiatives. Segregation of waste is the dominant protocol, and all three cities show a positive trend. The decentralization of wet waste treatment and sorting processes has facilitated material recovery. Centralized facilities, such as the waste-to-energy plant in Vishakhapatnam, the compressed biogas plant in Pune, and the biomethanation plant in Tirupati, are adding economic value to the system. Effective segregation and recovery have enabled scientific disposal, and advances have been made in the redemption of former dumpsites, with complete success in Tirupati.